2020
DOI: 10.3389/fpls.2020.00690
|View full text |Cite
|
Sign up to set email alerts
|

High Diversity of Cytospora Associated With Canker and Dieback of Rosaceae in China, With 10 New Species Described

Abstract: Cytospora canker is a destructive disease of numerous hosts and causes serious economic losses with a worldwide distribution. Identification of Cytospora species is difficult due to insufficient phylogenetic understanding and overlapped morphological characteristics. In this study, we provide an assessment of 23 Cytospora spp., which covered nine genera of Rosaceae, and focus on 13 species associated with symptomatic branch or twig canker and dieback disease in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 49 publications
(105 reference statements)
1
38
0
Order By: Relevance
“…Host affiliation has been primarily used as the delimitation in Cytospora in the early stage, and this has been proven uninformative because several Cytospora species have been discovered in a wide range of hosts (Adams et al, 2005 , 2006 ; Lawrence et al, 2018 ; Norphanphoun et al, 2018 ; Fan et al, 2020 ; Pan et al, 2020 ). Lawrence et al ( 2018 ) reported that Cytospora included generalist and specialist pathogens by taking C. chrysosperma and C. punicae as examples; however, a clear elucidation of the host ranges and distribution of Cytospora species will require a more exhaustive sampling of other coniferous trees from other regions of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host affiliation has been primarily used as the delimitation in Cytospora in the early stage, and this has been proven uninformative because several Cytospora species have been discovered in a wide range of hosts (Adams et al, 2005 , 2006 ; Lawrence et al, 2018 ; Norphanphoun et al, 2018 ; Fan et al, 2020 ; Pan et al, 2020 ). Lawrence et al ( 2018 ) reported that Cytospora included generalist and specialist pathogens by taking C. chrysosperma and C. punicae as examples; however, a clear elucidation of the host ranges and distribution of Cytospora species will require a more exhaustive sampling of other coniferous trees from other regions of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Lawrence et al ( 2018 ) reported 15 Cytospora species that infected fruit trees and crops using a multiphasic approach. Pan et al ( 2020 ) assessed 23 species of Cytospora associated with canker and dieback disease of Rosaceae members in China by six-locus phylogeny.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 672 species epithets of Cytospora have been recorded in the Index Fungorum (April 2021; ). Recent studies reported that approximately 150 species of Cytospora caused branch canker and dieback on more than 130 woody host species ( Spielman, 1985 ; Adams et al., 2002 ; Adams et al., 2005 ; Kirk et al., 2008 ; Fan et al., 2014a ; Fan et al., 2014b ; Fan et al., 2020 ; Pan et al., 2020 ; Pan et al., 2021 ). More than 1,137 species epithets of Diaporthe have been enumerated in the Index Fungorum (April 2021; ), and over 200 species have been accepted recently ( Udayanga et al., 2011 ; Dissanayake et al., 2017 ; Yang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study focuses on Diatrypaceae species in China, which is considered as a biodiversity hotspot with a high diversity for fungal species (Yang et al 2018;Fan et al 2020;Pan et al 2020). We hope that the descriptions and molecular data of Diatrypaceae in this study could provide a resource for future studies in this family.…”
Section: Discussionmentioning
confidence: 99%